The Influence of Maqāṣid Sharī‘ah Implementation on Satisfaction of Islamic Cooperatives’ Members - Bhinekawati, Risa; Ascarya, Ascarya; Firdaus, Achmad (Islamic Economics Department, Faculty of Islamic Economics and Business, Sunan Ampel State Islamic University, Surabaya Indonesia, 2024)
This study aims to elaborate on the application of indicators of five lower-order constructs of maqāṣid sharī‘ah in measuring the satisfaction of Islamic cooperative members. Subsequently, the Social Exchange Theory is used to explain the relationships among reciprocity, trust, maqāṣid sharī‘ah, and satisfaction. This study uses a quantitative approach by applying a two-stage reflective-formative analysis of Partial Least Square – Structural Equation Modeling (PLS-SEM). The data were collected from nine Islamic cooperatives in six provinces of Indonesia, where 247 valid questionnaires were processed and analyzed using SmartPLS software. The first stage of analysis confirmed that the indicators of five constructs of maqāṣid sharī‘ah (Religion, Life, Intellect, Lineage, and Trust) could be used as valid and reliable measurements for maqāṣid sharī‘ah. The second stage of the analysis found that maqāṣid sharī‘ah, together with reciprocity and trust, have a significant and positive influence on the satisfaction of sharī‘ah cooperative members. The results of this study can be generalized to the Islamic financial cooperatives. However, the application of the model to conventional cooperatives will require further research research. Consistent implementation of maqāṣid sharī‘ah would improve cooperatives members’ satisfaction and overall cooperatives performance. This study confirms that indicators and variables of maqāṣid sharī‘ah can be applied as measurements to analyze the satisfaction of Islamic cooperative members. It also provides empirical evidence of the application of Social Exchange Theory in the context of Islamic cooperatives, which has not been done by previous studies. Future studies are recommended to test this model in non-Islamic cooperatives, expand the dataset across Muslim-majority countries, and explore longitudinal impacts of maqāṣid-based governance on institutional sustainability.